Spirituality in ethical behavior towards the environment: A bibliometric analysis - Husamah, H.; Sanjaya, Andika Wahyu Bagus; Ramadhan, Rizki Sabilul Alif; Permana, Tutut Indria; Rahardjanto, Abdulkadir; Lestari, Nurdiyah; Shukri, Ahmad Adnan Mohd (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2025)
This study aims to analyze research trends related to spirituality and ethical behavior towards the environment through a bibliometric approach. Using data from 97 documents published between 1992 and 2024, this study answers eight research questions, including temporal distribution, dominant subject areas, most cited documents, most relevant sources, country collaboration patterns, main supporting institutions, keyword trends, and thematic patterns. The results show fluctuating publication growth, peaking in 2022. Arts and Humanities and Social Sciences are the most dominant fields, while the journal Worldviews: Environment, Culture, Religion is the main source. These findings provide strategic insights for the development of multidisciplinary research, global collaboration, and spirituality-based policies in supporting environmental sustainability. Spiritualitas dalam perilaku etis terhadap lingkungan: Analisis bibliometrik ABSTRAK: Penelitian ini bertujuan untuk menganalisis tren penelitian terkait spiritualitas dan perilaku etis terhadap lingkungan melalui pendekatan bibliometrik. Dengan menggunakan data dari 97 dokumen yang diterbitkan antara tahun 1992 dan 2024, penelitian ini menjawab delapan pertanyaan penelitian, meliputi distribusi temporal, bidang subjek dominan, dokumen yang paling banyak dikutip, sumber yang paling relevan, pola kolaborasi negara, lembaga pendukung utama, tren kata kunci, dan pola tematik. Hasilnya menunjukkan pertumbuhan publikasi yang fluktuatif, mencapai puncaknya pada tahun 2022. Bidang yang paling dominan adalah Seni dan Humaniora serta Ilmu Sosial, sedangkan jurnal Worldviews: Environment, Culture, Religion menjadi sumber utama.. Temuan ini memberikan wawasan strategis untuk pengembangan penelitian multidisiplin, kolaborasi global, dan kebijakan berbasis spiritualitas dalam mendukung keberlanjutan lingkungan.